2014
DOI: 10.1111/ina.12173
|View full text |Cite
|
Sign up to set email alerts
|

Very volatile organic compounds: an understudied class of indoor air pollutants

Abstract: Very volatile organic compounds (VVOCs), as categorized by the WHO, are an important subgroup of indoor pollutants and cover a wide spectrum of chemical substances. Some VVOCs are components of products commonly used indoors, some result from chemical reactions and some are reactive precursors of secondary products. Nevertheless, there is still no clear and internationally accepted definition of VVOCs. Current approaches are based on the boiling point, and the saturation vapor pressure or refer to analytical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(69 citation statements)
references
References 73 publications
1
62
1
5
Order By: Relevance
“…Methanol emissions from indoor surfaces have been measured for the first time in this study using the PTR‐ToF‐MS as this VOC cannot be measured by classical methods based on cartridge sampling and chromatographic analyses, due to its high volatility and its low molecular weight. In the literature, only a few previous studies reported measurements of methanol concentrations in an indoor environment, using the gas chromatography technique or the PTR‐MS technique …”
Section: Resultsmentioning
confidence: 99%
“…Methanol emissions from indoor surfaces have been measured for the first time in this study using the PTR‐ToF‐MS as this VOC cannot be measured by classical methods based on cartridge sampling and chromatographic analyses, due to its high volatility and its low molecular weight. In the literature, only a few previous studies reported measurements of methanol concentrations in an indoor environment, using the gas chromatography technique or the PTR‐MS technique …”
Section: Resultsmentioning
confidence: 99%
“…Among the indoor air pollutants are VOCs which are considered as harmful gases to human health (Salthammer, 2016). Consequently, healthy indoor air quality in our environment requires special attention.…”
Section: Adsorption By Nano-adsorptive Materialsmentioning
confidence: 99%
“…A recent work [13] has summarized the state of the art in the field of the Very Volatile Organic Compounds (VVOCs) -an important subgroup of indoor pollutants that involves a wide spectrum of chemical substances. However, there is still no clear definition of VVOCs and techniques for their assessment.…”
Section: Pollutants In the Indoor Environmentmentioning
confidence: 99%